Hierarchical Semiconductor Oxide Photocatalyst: A Case of the SnO2 Microflower - Liu, Yang; Jiao, Yang; Yin, Bosi; Zhang, Siwen; Qu, Fengyu; Wu, Xiang (Nano-Micro Letters, 2013)
Hierarchically assembled SnO2 microflowers were synthesized by a facile hydrothermal process. Field emission scanning electron microscope results showed these hierarchical nanostructures were built from two dimensional nanosheets with the thicknesses of about 50 nm. Photoluminescence spectrum of the as-obtained products demonstrated a strong visual emission peak at 564 nm. The photochemical measurement results indicated that the as-prepared sample exhibits excellent photocatalytic performance. These three dimensional SnO2 hierarchical nanostructures may have potential applications in waste water purification.